Melampaui Toleransi Mengeja Akseptansi Beragama - Asri, Syamsul (Aqidah-ta: Jurnal Ilmu Aqidah, 2024)
Tolerance, in this article, is articulated as a practice of living in inter-religious communities that is no longer capable of caring for and supporting religious diversity in Indonesia. Tolerance presupposes the ability of adherents of a religious identity to endure the wounds and suffering caused by the presence of adherents of another religious identity. This article aims to offer acceptance/penerimaan and akseptansi [in Bahasa Indonesia] as a daily discourse practice to replace tolerance. Acceptance presupposes that individuals and groups of adherents of a religious identity accept the presence of adherents of another religious identity as it is, without necessarily assuming that the presence of adherents of other religions inherently brings suffering to them. This goal is achieved by deploying the identity theories of Amartya Sen and Hubert Hermans, where for these two thinkers, religious identity can always be interpreted as the presence of oneself in the presence of another self without having to tolerate [announcing oneself that the other party always brings suffering to oneself] but rather accepting another identity as it is.